2019
DOI: 10.1186/s13018-019-1318-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on fracture lines of the quadrilateral plate based on fracture mapping

Abstract: Background Quadrilateral plate fractures are a challenging group of acetabular fractures to manage. However, there is little literature that describes the fracture lines of the quadrilateral plate. The aim of this study was to explore the fracture lines of the quadrilateral plate and relevant clinical significance. Methods CT data from a series of acetabular fractures were retrospectively analyzed. According to the X-ray, CT, and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In addition, this technique was widely used in the acetabulum. Yang et al [ 12 , 13 ] established a frequency map of acetabular both-column fractures and quadrilateral fractures to help surgeons gain insights into the surgery. Cho et al [ 14 ] evaluated the characteristics of isolated PW fractures of the acetabulum with a cohort of 51 patients to show fracture patterns and recurrent fracture zones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this technique was widely used in the acetabulum. Yang et al [ 12 , 13 ] established a frequency map of acetabular both-column fractures and quadrilateral fractures to help surgeons gain insights into the surgery. Cho et al [ 14 ] evaluated the characteristics of isolated PW fractures of the acetabulum with a cohort of 51 patients to show fracture patterns and recurrent fracture zones.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture mapping can record the size, shapes, numbers, and orientations of fracture fragments, and help surgeons determine the optimal treatment (5). To date, fracture mapping has been applied to scapular, tibial, hip, and acetabular fractures (6)(7)(8)(9)(10)(11). However, there have been no reports concerning fracture mapping for the treatment of calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al . 27 identified the borders of the quadrilateral plate, which was same as ElNahal et al ., and described a fracture map of QLS. Guyton and Perez 28 considered QLS to be the medial wall of acetabulum, and mentioned that it was located near the femoral head limiting the options for its fixation.…”
Section: Discussionmentioning
confidence: 92%
“…ElNahal, et al 23 considered it as the trapezoidal area and described that the QLS extended from the pelvic brim superiorly to a line joining the ischial spine and obturator foramen inferiorly, and is bound by the greater sciatic notch posteriorly and the obturator foramen anteriorly. Yang et al 27 identified the borders of the quadrilateral plate, which was same as ElNahal et al, and described a fracture map of QLS. Guyton and Perez 28 considered QLS to be the medial wall of acetabulum, and mentioned that it was located near the femoral head limiting the options for its fixation.…”
Section: Definition Of Qlsmentioning
confidence: 97%